The evaluation of AdBlock technique implementation for enterprise network environment - Mohd Iskandar Bin Samsuddin; Mohamad Yusof Darus; Shamsul J Elias; Abidah Hj Mat Taib; Norkhushaini Awang; Roshidi Din (Institute of Advanced Engineering and Science, 2019)
This paper presents the evaluation of AdBlock technique implementation for enterprise network environment. This study has presented the impact of web browsing activities where it is the most active traffic where is consumed the highest inbound bandwidth usage in enterprise network environment. We can conclude that DNS AdBlock is the best solution for enterprise network environment in term of blocking advertisement compare to extension adblock. Adblock technique also reduce network data request by comparing front-end solution (browser extension AdBlock) at client web browser and networks level adblock. The parameters such as HTTP request, TCP connection and network bandwidth are being examined to measure the effectiveness of blocking online advertisement. Both techniques perform the reduction of traffics and bandwidth utilization. The result shows that DNS AdBlock is the most effective in blocking online advertisement using the examined parameters. DNS AdBlock can sustain the usage of web browsing activity for enterprise network and also generate substantial saving across several fonts. This study has identified current web browsing trends traffic in enterprise network where it consumed 50 percent in average. This number increased when industries are moving to cloud web-based consumption. However, industries such as educational sector, web browsing traffic is one of connectivity that enterprises network should be investing to support openness and heavy traffic from educational users.